Seven new species of the genus Epitrimerus Nalepa (Acari: Eriophyidae: Phyllocoptinae) from China - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2007)
Seven new species in the genus Epitrimerus Nalepa from China are described and illustrated, namely Epitrimerus dendranthemae sp. nov. on Dendranthema indicum (L.) Des Moul. (Compositae); Epitrimerus vescae sp. nov. on Fragaria vesca L. (Rosaceae); Epitrimerus argyris sp. nov. on Artemisia argyri Lévl. & Vant. (Compositae); Epitrimerus lonicerae sp. nov. on Lonicera sp L. (Caprifoliaceae); Epitrimerus microcarpae sp. nov. on Ficus microcarpa L. f. (Moraceae); Epitrimerus cotoneasteri sp. nov. on Cotoneaster sp. B. Ehrhart (Rosaceae) and Epitrimerus integrae sp. nov. on Salix integra Thunb. (Salicaceae). A key to the species of Epitrimerus in China is provided. The eriophyoid mite species described here are vagrants on the leaf surfaces of their host plants.